2019
DOI: 10.22608/apo.2017436
|View full text |Cite
|
Sign up to set email alerts
|

Management of Retinopathy of Prematurity—Use of Anti-VEGF Therapy

Abstract: Retinopathy of prematurity (ROP) is a leading cause of childhood blindness worldwide. Although laser photocoagulation re-mains the gold standard for treating threshold and prethreshold disease (type 1 ROP), the off-label use of anti‒vascular endothelial growth factor (anti-VEGF) therapy to treat ROP is increasing. Benefits include acute regression of ROP, growth of retinal vasculature beyond the demarcation line, lesser degree of myopia and peripheral visual field loss, and avoidance of sedation and intubation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 88 publications
0
27
0
1
Order By: Relevance
“…1 Characterised by retinal ischaemia, aberrant angiogenesis, fibrovascular proliferation and progressive vitreoretinal traction, ROP accounts for 14% and 20% of cases of childhood blindness in the USA and developing countries, respectively. 2 ROP is a unique retinal vascular proliferative disease occurring in premature and low birthweight infants. 3 Retinal vascularisation normally occurs at around 12 weeks of gestation and is completed by 36-40 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…1 Characterised by retinal ischaemia, aberrant angiogenesis, fibrovascular proliferation and progressive vitreoretinal traction, ROP accounts for 14% and 20% of cases of childhood blindness in the USA and developing countries, respectively. 2 ROP is a unique retinal vascular proliferative disease occurring in premature and low birthweight infants. 3 Retinal vascularisation normally occurs at around 12 weeks of gestation and is completed by 36-40 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also demonstrated possible adverse effects of anti-VEGF therapy in ROP, including suppression of organ development and long-term systemic safety 39, 40. However, it is obvious that regulating VEGF is beneficial for ROP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…ROP shares some pathogenic features seen with DR. Therapeutic efficacy of anti-VEGFs in treating and managing ROP underlines the importance of VEGF signalling (Tran et al, 2018) and also suggests a role for galectins.…”
Section: Other Retinopathies With Vascular Aetiologymentioning
confidence: 99%